Sustainability of Off-Grid Photovoltaic Systems for Rural Electrification in Developing Countries: A Review - Christin-Feron, S (Multidisciplinary Digital Publishing Institute (MDPI), 2016)
A review on rural electrification programs and projects based on off-grid Photovoltaic (PV) systems, including Solar Pico Systems (SPS) and Solar Home Systems (SHS) in Developing Countries (DCs) was conducted. The goal was to highlight the main multidimensional drawbacks that may constrain the sustainability of these systems. Four dimensions of sustainability (institutional, economic, environmental and socio-cultural) were considered in this review. It was found that institutional flaws (such as the scarcity of durability/stability and enforcement of formal institutions, weak regulations or standards, incomplete decentralization/participation and the lack of institutional adaptability) seriously compromise the sustainability of rural electrification efforts in DCs. While the lack of an effective focalized subsidy scheme (e.g., cross-tariff scheme) for the electricity tariffs of the poor population often made projects economically unsustainable, the scarcity of environmental awareness, regulations or incentives has often turned presumably clean energy technologies into environmentally unsustainable projects. Progress regarding social acceptance, accuracy and cultural justice is urgently needed for ensuring the socio-cultural sustainability of rural electrification efforts in DCs. This review may help stakeholders to identify and (based on prior experiences) address the most severe drawbacks affecting the sustainability of rural electrification efforts in DCs. © 2016 by the author.